A Study on The Crack Behavior of Baggase-Polyester Composites - Rozi Saferi; Asmara Yanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2017)
The development of composite technology has begun to change nowadays, from composite fiber-synthesized to composite natural fiber fabrics. Natural baggase fiber has the opportunity to be developed as a strengthening medium in polymer resins. The purpose of this study were to know the effect of fiber orientation to maximum critical load for different initial crack lengths, to know elastic energy of composite material having fiber orientation varied at the time of loading and to know the effect of fiber orientation on fracture toughness for composite material. In this paper, it’s used 1.5mm diameter sugarcane fibers and the polyester matrix. The fraction volume of fiber and resin used is 5%: 95%. Fiber is given 20% NaOH treatment. Then the fiber is arranged with orientation 0/90º and 0/45º. While the bending test specimen is in accordance with ASTM-D5045 standard, the size of the specimen dimension is 125 mm long, 30 mm wide and 10 mm thick; with crack variations are 7mm, 9mm, 11mm, 13mm, and 15mm. It’s could be concluded that the critical load will decrease as the initial crack length increases. Composite material with 0/90º fiber orientation has elastic energy greater than composite with 45º fiber orientation. And crack propagation rate in composite material with fiber orientation 0/90º is faster than composite with 0/45º orientation.